EVALUASI KETAHANAN TERHADAP PENYAKIT KUDIS DAN PRODUKSI BEBERAPA KULTIVAR UBIJALAR - Eko Agus Martanto; Adelin Tanati; Samen Baan (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2016)
Evaluation of scab disease resistance and production on sweet potato cultivars. This study was aimed to determine the resistance of local sweet potato cultivars to scab disease in West Papua and the cultivar production. Research was carried out for 6.5 months starting in April 2014. Evaluation of resistance of local sweet potato cultivars and production was designed using a randomized complete block design (RCBD) with three replications. The treatment consists of six local cultivars, namely Mouwebsi, Kuyage-2, Bonsasarai, Inanwatan-4, Wonembai, and Abomourow. There was no inoculation treatment on the field because Papua was endemic region to the scab disease. Data analysis was performed using analysis of variance (ANOVA), followed by DMRT test at level of 95%. Cultivars tested had different responses to the long tendrils of parameters and number of branches. The intensity of the disease in Bonsasarai cultivars was 31.7% (moderately resistant), while in Mouwebsi was 13.75%, Wonembai 8.33%, Kuyage-2 0.42%, Abomourow and Inanwatan-4, 0% categorized as resistant cultivars. The tuber weight of Abomourow (4.55 ton/ha) was higher than that of Mouwebsi (3.80 ton/ha), Wonembai (3.62 ton/ha), BonsasaraiÂ (2.28 ton/ha), and Inanwatan-4 (1.12 ton/ha).